Pelvic floor disorders stop women exercising: A survey of 4556 symptomatic women. Issue 12 (December 2021) - Dakic, Jodie G.; Cook, Jill; Hay-Smith, Jean; Lin, Kuan-Yin; Frawley, Helena
Abstract: Objectives: To establish the impact of pelvic floor (PF) symptoms (urinary incontinence [UI], anal incontinence [AI] and pelvic organ prolapse [POP]) on exercise participation in women. Design: Observational, cross-sectional survey. Methods: Australian, 18- to 65-year-old women with self-identified PF symptoms during exercise (current, past or fear of) were included. This survey included validated questionnaires: Questionnaire for female Urinary Incontinence Diagnosis, Incontinence Severity Index, Pelvic Floor Bother Questionnaire, International Physical Activity Questionnaire and purpose-designed questions on the impact of PF symptoms on sport/exercise participation. Analysis utilised descriptive statistics. Chi-square tests for independence and t -tests were used to explore differences between groups. Results: Of 4556 women, 46% stopped exercise they had previously participated in due to their PF symptoms. Urinary incontinence had the largest impact; 41% with UI, followed by 37% with POP and 26% with AI stopped at least one form of exercise. Forty-two percent of women who experienced symptoms in high-impact sports stopped participation (versus low-impact: 21%). Sports commonly ceased included volleyball (63%), racquet-sports (57%) and basketball (54%). Exercise cessation was reported amongst younger (18–25 years: 35%) and nulliparous women (31%). Common exercise modifications included lowering the intensity (58%) or frequency (34%) of participation or changing to a low-impact form of sport/exercise (45%). Conclusions: Pelvic floor symptoms stop women of all ages and levels of participation from exercising. High-impact sports were most affected but low-impact sports were also ceased. Symptomatic women also modify exercise to less vigorous/frequent participation, which may place them at risk of physical inactivity, and chronic illness.